Preparation method and application of ultra-low palladium-loaded cerium dioxide cubic electrocatalyst
By preparing ultra-low palladium-supported ceria cube electrocatalysts, the scarcity and high price of precious metal catalysts in AEM electrolytic hydrogen production technology are solved, and high-efficiency electrocatalytic oxygen evolution reaction and stability under alkaline conditions are achieved, reducing the and the amount of palladium used.
Patent Information
- Application Number
- CN202411304159.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-20
AI Technical Summary
The scarcity and high price of precious metal catalysts in AEM electrolytic hydrogen production technology are not conducive to large-scale industrial use, and the catalytic activity and stability of non-precious metal catalysts still need to be improved.
The preparation method of ultra-low palladium-supported ceria cube electrocatalyst is prepared by mixing the cerium source with a strong alkali solution, dispersing it with the palladium-containing solution after reaction, adjusting the pH, aging and heat treatment, and preparing Pd/CeO2 nanocube catalyst. It has ultra-low Pd load and high dispersion.
Excellent electrocatalytic oxygen evolution reaction performance and high electrochemical stability under alkaline conditions are achieved, reducing the amount and cost of palladium, and improving the activity and stability of the catalyst.
Smart Images

Figure HDA0005048613390000011 
Figure HDA0005048613390000012 
Figure HDA0005048613390000013
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrocatalysts, and in particular relates to a preparation method and application of an ultra-low palladium-loaded cerium dioxide cubic electrocatalyst. Background Art
[0002] As a clean, environmentally friendly, high calorific value, safe and rich secondary energy, hydrogen is an ideal alternative to traditional fossil fuels and is gradually becoming one of the important carriers of global energy transformation and development. It can be widely used in energy storage, transportation, electricity, chemical product production and other fields. Among them, the technology of hydrogen production by electrolysis of water is mature, carbon-free and pollution-free. The produced hydrogen is of high purity and few impurities, and is regarded as a green and efficient solution.
[0003] Traditional alkaline electrolysis hydrogen production technology (ALK) has difficulty responding to transient loads and has low current density. Proton exchange membrane electrolysis hydrogen production technology (PEM) requires expensive perfluorosulfonic acid proton membranes and precious metal catalysts, resulting in high operating costs. Anion membrane electrolysis hydrogen production technology (AEM) can use pure water or low-concentration alkaline aqueous solutions as electrolytes, alleviating the corrosion of strong alkaline solutions to equipment. At the same time, this technology does not require the use of expensive perfluorosulfonic acid membranes and precious metal catalysts, which can further reduce material costs. AEM electrolysis hydrogen production technology combines easy operation when coupled with renewable energy, and has the advantages of low cost, fast start and stop, and low energy consumption. At the same time, it can achieve current and efficiency comparable to PEM, and is considered to be the most promising technology for large-scale hydrogen production in the future.
[0004] However, AEM electrolysis hydrogen production technology is still in the development stage, and there are still many key issues that need to be solved. Early AEM catalyst research mainly focused on composite materials of precious metal elements such as Pt and Ir, but the scarcity and high price of precious metals are not conducive to their large-scale industrial use. The non-precious metal catalysts currently developed are relatively cheap, but the catalytic activity and stability still need to be improved. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a method for preparing an ultra-low palladium-loaded cerium dioxide cubic electrocatalyst and its application. 2 The nanocubes can act as oxygen evolution catalysts with ultralow Pd loading.
[0006] The present invention provides a method for preparing an ultra-low palladium-loaded ceria cubic electrocatalyst, comprising the following steps:
[0007] 1) mixing a cerium source and a strong alkaline solution, reacting, washing, drying, and heat treating the product to obtain a cerium dioxide carrier;
[0008] 2) mixing the palladium-containing solution and the cerium dioxide carrier dispersion, stirring, adjusting the pH to 9.5-10.5, aging, filtering, and obtaining a powder;
[0009] 3) washing, drying and heat treating the powder to obtain an ultra-low palladium-loaded ceria cubic electrocatalyst.
[0010] The present invention mixes a cerium source and a strong alkaline solution, reacts, washes, dries, and heat treats the product to obtain a cerium dioxide carrier. In the present invention, the cerium source is selected from Ce(NO 3 ) 3 6H 2 O or CeCl·7H 2 O; the strong base is selected from NaOH or KOH; the molar ratio of the cerium source and the strong base is (3-5): (0.5-1.5). The present invention preferably adds the cerium source dropwise to the strong base solution and stirs for 55-65 minutes to obtain a homogeneous solution. The present invention transfers the homogeneous solution to a polytetrafluoroethylene liner for reaction, and the reaction temperature is 180-200°C and the time is 18-24 hours. After the reaction is naturally cooled to room temperature, the present invention uses deionized water to filter and wash the solid obtained by the reaction to wash away excess sodium ions. The present invention preferably dries at 80-100°C for 18-24 hours, and heat treats the dried powder at 400-500°C for 4-8 hours in an air atmosphere to obtain a cerium dioxide carrier (CeO 2 -Cube); the cerium dioxide carrier is in the shape of a nanocube.
[0011] After obtaining the cerium dioxide carrier, the present invention mixes the palladium-containing solution and the cerium dioxide carrier dispersion liquid, stirs, adjusts the pH to 9.5-10.5, ages, and filters to obtain powder.
[0012] The palladium-containing solution of the present invention is selected from Pd(NO 3 ) 2 Solution or PdCl 2 The solvent in the palladium-containing solution is water. The present invention ultrasonically disperses the cerium dioxide carrier in superionized water for 25 to 35 minutes. The mass ratio of palladium in the palladium-containing solution to the cerium dioxide carrier in the cerium dioxide carrier dispersion is (0.01 to 0.015): (1 to 1.2).
[0013] The present invention preferably adds the cerium dioxide carrier dispersion into the palladium-containing solution and stirs for 25 to 35 minutes to obtain a palladium-cerium mixed solution; the present invention uses a NaOH solution to adjust the pH of the palladium-cerium mixed solution to 9.5 to 10.5, and the concentration of the NaOH solution is 0.2 mol / L.
[0014] The aging temperature in the present invention is preferably 40-60°C, and the time is 2-4h. After the aging is completed, the filtered powder is washed with deionized water for multiple times and then dried; the present invention is dried in an oven; the drying temperature is 80-100°C, and the time is 18-24h; the heat treatment temperature is 400-500°C, and the time is 2-4h; the heat treatment atmosphere is H 2 / Ar mixed atmosphere.
[0015] The Pd content in the ultra-low palladium-loaded cerium dioxide cubic electrocatalyst prepared by the method provided by the invention is 0.50-0.65%; the average particle size of the Pd nanoparticles is 1.6-1.75nm, and the dispersion is 64-70%.
[0016] The present invention provides an application of an ultra-low palladium-loaded cerium dioxide cubic electrocatalyst prepared by the preparation method described in the above technical scheme in electrolysis of water.
[0017] The present invention provides a method for preparing an ultra-low palladium-loaded ceria cubic electrocatalyst, comprising the following steps: 1) mixing a cerium source and a strong alkaline solution, reacting, washing, drying, and heat-treating the product to obtain a ceria carrier; 2) mixing a palladium-containing solution and a ceria carrier dispersion, stirring, adjusting the pH to 9.5-10.5, aging, filtering, and obtaining a powder; 3) washing, drying, and heat-treating the powder to obtain an ultra-low palladium-loaded ceria cubic electrocatalyst. The electrocatalyst prepared by the method has a low palladium content and low cost; under alkaline conditions, the electrocatalytic oxygen evolution reaction performance is excellent and the electrochemical stability is high. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The CeO prepared in Example 1 of the present invention 2 -Scanning electron microscope image (SEM) of Cube;
[0019] Figure 2 Pd / CeO prepared in Example 1 of the present invention 2 - Transmission electron microscopy (TEM) image of Cube catalyst;
[0020] Figure 3 The Pd / CeO prepared in Example 1 of the present invention in 1 mol / L KOH electrolyte 2 -OER performance test of Cube catalyst;
[0021] Figure 4 Pd / CeO prepared in Example 1 of the present invention 2 -Cube catalyst stability test results;
[0022] Figure 5 Pd / CeO prepared in Example 1 of the present invention 2-Cube catalyst performance comparison chart before and after reaction;
[0023] Figure 6 Pd / CeO prepared in Examples 1 to 3 of the present invention 2 -Electrochemical performance test diagram of Cube catalyst. DETAILED DESCRIPTION
[0024] In order to further illustrate the present invention, the preparation method and application of an ultra-low palladium-loaded ceria cubic electrocatalyst provided by the present invention are described in detail below in combination with examples, but they should not be understood as limiting the scope of protection of the present invention.
[0025] Example 1
[0026] 1. Weigh 4mmol Ce(NO 3 ) 3 6H 2 O and 1 mol NaOH were added to 10 mL and 70 mL of deionized water, respectively, and stirred to dissolve. Then, the Ce solution was added dropwise to the NaOH solution and stirred for 60 min to obtain a homogeneous solution. Then it was transferred to a 100 mL polytetrafluoroethylene liner and reacted at 180 ° C for 24 h. After the reaction was cooled naturally to room temperature, the powder was washed with deionized water to wash away excess Na ions, and then dried in an oven at 80 ° C for 24 h. Finally, the dried powder was heat treated at 500 ° C for 4 h under a nitrogen atmosphere to obtain a nanocubic morphology of cerium dioxide carrier (CeO 2 -Cube).
[0027] Figure 1 This is a SEM image of the cerium dioxide support synthesized in Example 1 of the present invention;
[0028] 2. Deposition of Pd nanoparticles onto CeO by deposition-precipitation method 2 -Cube carrier, the specific method is as follows: First, take 1g of Pd (NO 3 ) 2 hydrate, prepared into 50mL of Pd(NO 3 ) 2 Then, take 5 mL of Pd(NO 3 ) 2 The aqueous solution was dispersed in 100 mL of deionized water and stirred evenly. 1 g CeO 2 -Cube was ultrasonically dispersed in deionized water for 30 min and then added to Pd(NO 3 ) 2The mixture was stirred for 60 min in an aqueous solution. The pH of the mixed solution of palladium and cerium was then adjusted to 10 with a 0.2 M NaOH solution, and then aged at 40 °C for 4 h. The filtered powder was then washed several times with deionized water and dried in an oven at 100 °C for 18 h. 2 / Ar atmosphere, and heat treated at 400℃ for 4h to obtain Pd / CeO 2 -Cube Catalyst.
[0029] Figure 2 The Pd / CeO prepared in Example 1 of the present invention 2 -TEM image of Cube catalyst;
[0030] The present invention uses ICP-MS instrument to analyze the synthesized Pd / CeO 2 -Cube catalyst was tested for Pd content, and the results showed that the Pd content was about 0.60wt%, the average particle size of Pd nanoparticles was 1.69nm, and the dispersion was 66.3%.
[0031] application:
[0032] In order to study the Pd / CeO 2 -Cube catalyst is used in water electrolysis. The catalyst is prepared into slurry and coated on the electrode surface. The catalyst is tested by cyclic voltammetry using an electrochemical workstation.
[0033] Slurry preparation: First, weigh 7 mg of catalyst sample and 3 mg of carbon black, disperse them in 970 μL of isopropanol solution, add 30 μL of Nafion solution after ultrasonic treatment for 10 min, and then ultrasonicate the mixed solution for 30 min to obtain the final slurry. Take 20 μL of slurry solution and drop it on the nickel foam electrode. After natural drying, it can be tested.
[0034] Test: The electrochemical oxygen evolution performance test was carried out in a three-electrode system, and the solution was 1M KOH solution. Before the test, nitrogen was introduced into the electrolyte for 30 minutes until it was saturated. Before the electrocatalytic oxygen evolution reaction (OER) test, the working electrode was activated by 20 cycles of cyclic voltammetry (CV), and then a polarization curve test (LSV) was performed at a scan rate of 5mV s -1 .
[0035] Test results: The Pd / CeO 2 -Cube catalyst showed excellent OER catalytic performance under alkaline conditions. 2 At a current density of 1.3 Å, the oxygen evolution overpotential is 360 mV, which is lower than that of some commercial precious metal catalysts (RuO 2 , 440mV) is more active (see Figure 3 ). 2 -Cube catalyst stability test, it can be seen that at 10mA / cm 2 At a current density of 1.3 Å, the potential did not increase significantly after 30 h of OER reaction (see Figure 4 ), and the Pd / CeO 2 -Cube catalyst has a high overlap in LSV curves before and after OER reaction (see Figure 5 ), indicating that the catalyst has good stability and durability, which provides a good prospect for the actual industrial application of the material and also provides guidance for the design and synthesis of the further improvement of this series of materials.
[0036] Example 2
[0037] 1. Weigh 3mmol Ce(NO 3 ) 3 6H 2 O and 1 mol NaOH were added to 10 mL and 70 mL of deionized water, respectively, and stirred to dissolve. Then, the Ce solution was added dropwise to the NaOH solution and stirred for 60 min to obtain a homogeneous solution. Then, it was transferred to a 100 mL polytetrafluoroethylene liner and reacted at 200 ° C for 18 h. After the reaction was cooled naturally to room temperature, the powder was washed with deionized water to wash away excess Na ions, and then dried in an oven at 100 ° C for 18 h. Finally, the dried powder was heat treated at 400 ° C for 4 h under a nitrogen atmosphere to obtain a nanocubic morphology of cerium dioxide carrier (CeO 2 -Cube).
[0038] 2. Deposition of Pd nanoparticles onto CeO by deposition-precipitation method 2 -Cube carrier, the specific method is as follows: First, take 1g of Pd (NO 3 ) 2 hydrate, prepared into 50mL of Pd(NO 3 ) 2 Then, take 5 mL of Pd(NO 3 ) 2 The aqueous solution was dispersed in 100 mL of deionized water and stirred evenly. 1 g CeO 2 -Cube was ultrasonically dispersed in deionized water for 30 min and then added to Pd(NO 3 ) 2The mixture was stirred for 60 min in an aqueous solution. The pH of the mixed solution of palladium and cerium was then adjusted to 10 with a 0.2 M NaOH solution, and then aged at 60 °C for 2 h. The filtered powder was then washed several times with deionized water and dried in an oven at 100 °C for 18 h. 2 / Ar atmosphere, and heat treated at 500℃ for 2h to obtain Pd / CeO 2 -Cube Catalyst.
[0039] Example 3
[0040] 1. Weigh 3 mmol Ce(NO 3 ) 3 6H 2 O and 1 mol NaOH were added to 10 mL and 70 mL of deionized water, respectively, and stirred to dissolve. Then, the Ce solution was added dropwise to the NaOH solution and stirred for 60 min to obtain a homogeneous solution. It was then transferred to a 100 mL polytetrafluoroethylene liner and reacted at 200 ° C for 24 h. After the reaction was cooled naturally to room temperature, the powder was washed with deionized water to remove excess Na ions, and then dried in an oven at 80 ° C for 24 h. Finally, the dried powder was heat treated at 450 ° C for 3 h under a nitrogen atmosphere to obtain a nanocubic morphology of cerium dioxide carrier (CeO 2 -Cube).
[0041] 2. Deposition of Pd nanoparticles onto CeO by deposition-precipitation method 2 -Cube carrier, the specific method is as follows: First, take 1g of Pd (NO 3 ) 2 hydrate, prepared into 50mL of Pd(NO 3 ) 2 Then, take 5 mL of Pd(NO 3 ) 2 The aqueous solution was dispersed in 100 mL of deionized water and stirred evenly. 1 g CeO 2 -Cube was ultrasonically dispersed in deionized water for 30 min and then added to Pd(NO 3 ) 2 The mixture was stirred for 60 min in an aqueous solution. The pH of the mixed solution of palladium and cerium was then adjusted to 10 with a 0.2 M NaOH solution, and then aged at 60 °C for 4 h. The filtered powder was then washed several times with deionized water and dried in an oven at 100 °C for 18 h. 2 After heat treatment at 500℃ for 4h in / Ar atmosphere, Pd / CeO 2 -Cube Catalyst.
[0042] Figure 6 Pd / CeO prepared in Examples 1 to 3 of the present invention 2 -Cube catalyst electrochemical performance test diagram. Figure 6 It can be seen that the Pd / CeO prepared by this method 2 -Cube catalysts all have excellent OER catalytic activity at 50mA / cm 2 At a current density of 1.3 Å, the oxygen evolution overpotential is in the range of 360-376 mV, and the catalytic activity is comparable to that of commercial RuO 2 (440mV) higher.
[0043] It can be seen from the above embodiments that the present invention provides a method for preparing an ultra-low palladium-loaded ceria cubic electrocatalyst, comprising the following steps: 1) mixing a cerium source and a strong alkaline solution, reacting, washing, drying, and heat-treating the product to obtain a ceria carrier; 2) mixing a palladium-containing solution and a ceria carrier dispersion, stirring, adjusting the pH to 9.5-10.5, aging, filtering, and obtaining a powder; 3) washing, drying, and heat-treating the powder to obtain an ultra-low palladium-loaded ceria cubic electrocatalyst. The electrocatalyst prepared by this method has a low palladium content and low cost; under alkaline conditions, the electrocatalytic oxygen evolution reaction performance is excellent and the electrochemical stability is high.
[0044] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an ultra-low palladium-loaded ceria cubic electrocatalyst, comprising the following steps: 1) mixing a cerium source and a strong alkaline solution, reacting, washing, drying, and heat treating the product to obtain a cerium dioxide carrier; 2) mixing the palladium-containing solution and the cerium dioxide carrier dispersion, stirring, adjusting the pH to 9.5-10.5, aging, filtering, and obtaining a powder; 3) washing, drying and heat treating the powder to obtain an ultra-low palladium-loaded ceria cubic electrocatalyst.
2. The preparation method according to claim 1, characterized in that: In step 1), the cerium source is selected from Ce(NO3)3·6H2O or CeCl·7H2O; The strong base is selected from NaOH or KOH; The molar ratio of the cerium source to the strong base is (3-5):(0.5-1.5).
3. The preparation method according to claim 1, characterized in that: In step 1), the reaction temperature is 180-200°C and the reaction time is 18-24h; The drying temperature is 80-100°C and the drying time is 18-24h; The heat treatment temperature is 400-500° C. and the time is 4-8 hours.
4. The preparation method according to claim 1, characterized in that: In step 2), the palladium-containing solution is selected from a Pd(NO3)2 solution or a PdCl2 solution; The mass ratio of palladium in the palladium-containing solution to the cerium dioxide carrier in the cerium dioxide carrier dispersion is (0.01-0.015):(1-1.2).
5. The preparation method according to claim 1, characterized in that: In step 2), the aging temperature is 40-60° C. and the aging time is 2-4 hours.
6. The preparation method according to claim 1, characterized in that: In step 3), the drying temperature is 95 to 105° C. and the drying time is 18 to 24 hours; The heat treatment temperature is 400-500°C and the time is 2-4h.
7. The preparation method according to claim 1, characterized in that: The Pd content in the ultra-low Pd-loaded ceria cubic electrocatalyst is 0.50-0.65%; The average particle size of the Pd nanoparticles is 1.6-1.75 nm, and the dispersion degree is 64-70%.
8. Use of an ultra-low palladium-loaded ceria cubic electrocatalyst prepared by the preparation method according to any one of claims 1 to 7 in electrolysis of water.
